Hubungan Kandungan C-Organik dengan Kelimpahan Kepiting Uca di Kawasan Mangrove Pulau Penyu, Tanjung Benoa, Bali - Kusuma, I Gusti Agung Made Divasena; Surya Indrawan, Gede; Pratama Atmaja, Putu Satya (Journal of Marine Research and Technology, 2025)
Mangroves are a primary habitat for Uca crabs, which typically live in substrates and are residents of mangrove forests. This study aimed to investigate the relationship between soil organic carbon (C-organic) content and the abundance of Uca crabs in Pulau Penyu, Tanjung Benoa, Bali. The research was conducted in January 2024 at three stations using a 100-meter transect line with ten 1x1 meter plots. Environmental parameters measured included C-organic content, substrate texture, temperature, pH, and salinity. This study found four crabs: Uca coarctata, Uca annulipes, Uca vomeris, and Uca dussumeri. Observations showed the highest abundance in Uca annulipes (6 ind/m² at station III) and the lowest in Uca vomeris (3 ind/m² at station II). Based on station analysis, the highest abundance was found at station I (18 ind/m²) and the lowest at station II (16 ind/m²). The diversity index (H’), evenness (E), and dominance (C) of Uca crabs were calculated for each station, showing moderate diversity (1.33–1.37), moderate evenness (0.47–0.51), and low dominance (0.26–0.28). Environmental parameters showed temperature variations (34.2–35.3°C), pH (6.1–6.4), salinity (30.5–35.7 ppt), and substrate type (sandy clay loam to loamy sand). Linear regression analysis indicated a positive relationship between Uca crab abundance and soil C-organic content, showing that the variation in soil C-organic content can explain 97.55% of the variation in Uca crab abundance.